Translators and interpreters, translation and interpretation - Schouten, Maria Johanna Christina (2013)
Discussion of the processes of communication in Southeast Asia, in the 16th-18th centuries, between the Portuguese seafarers and the local population, mainly traders and political rulers. Central is the role of the interpreters, as intermediaries ad as translators not just of language but also of customs and etiquette. In addition, the special position and features of Malay and lateron Portuguese as a contact language in the archipelago are major subjects.